Through the Looking Glass or Can the Revolution Be Overcome? Discussing the book: Revolution and Its Overcoming: Essays on the History of the Russian Mentality: monograph by E.M. Kozhokin. Moscow: MGIMO-University, 2020. 270 p. (in Russian) - M. N. Mokhovikova (Сравнительная политика, 2021)
Discussing the monograph “Revolution and Its Overcoming: Essays on the History of the Russian Mentality” by Doctor of History, Professor E.M. Kozhokin. The collection of seven essays related to one cross-cutting theme of the formation of revolutionary ideas in Russian society is considered from the perspective of a modern reader.